Tumor Necrosis Factor Receptor 1 Is Required for Human Umbilical Cord–Derived Mesenchymal Stem Cell–Mediated Rheumatoid Arthritis Therapy - Guangyang Liu; Herui Wang; Chenliang Zhang; Xin Li; Yi Mi; Yaoyao Chen; Liqiang Xu; Li Miao; Haomiao Long; Yongjun Liu (Cell Transplantation)
Rheumatoid arthritis (RA) is a systemic, chronic inflammatory disease characterized by altered levels of inflammatory cytokines. One of the key cytokines involved in the pathogenesis of RA is tumor necrosis factor α (TNF-α), which plays a crucial role in the differentiation of T cells and B cells and serves as a primary trigger of inflammation and joint damage in RA. Human umbilical cord-derived mesenchymal stem cells (hUC-MSCs) have shown potential in alleviating the symptoms of RA. Previous in vitro studies indicate that TNF-α secreted by T cells can activate NF-κB in human MSCs, thereby triggering the immunoregulatory capacity of MSCs in a manner dependent on tumor necrosis factor receptor 1 (TNFR1). Inspired by these findings, we aimed to evaluate whether TNFR1 determine the therapeutic effects of hUC-MSCs on RA. First, we investigated whether TNFR1 is necessary for hUC-MSCs to inhibit TNF-α production of PBMCs, a source of elevated TNF-α in patients. Through coculture experiment, we confirmed that this inhibition was dependent on TNFR1. Subsequently, we administered hUC-MSCs or siTNFR1-MSCs to DBA/1J male mice with collagen-induced arthritis. The results indicated that hUC-MSCs significantly alleviated the pathological features of RA and suppressed the inflammatory cytokines IFN-γ, TNF-α, and IL-6 in peripheral blood, also in a manner dependent on TNFR1 either. Given the dramatic pathologic differences between hUC-MSCs and siTNFR1-MSCs treatments, we questioned whether production of growth factors and chemokines was significantly influenced by TNFR1. Consequently, we stimulated hUC-MSCs or siTNFR1-MSCs through IFN-γ, TNF-α, and IL-6, and profiled growth factors and chemokines in serum, which revealed significant changes of hepatocyte growth factor (HGF) and keratinocyte growth factor (KGF), as well as chemokines CXCL9, CXCL10, IL-8, and RANTES. In summary, our findings suggest that TNFR1 may determine whether hUC-MSCs will gain abilities of anti-inflammation and tissue regeneration.